THE INFLUENCE OF STORE RATING, DELIVERY SERVICE, AND STORE CATEGORY TOWARD SALES LEVEL IN TOKOPEDIA - Dativa Averina Santie (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2023)
This study aims to find out what variables are significant related to the level of sales on one of the e-commerce platforms in Indonesia, Tokopedia, by using the variables Store Rating, Delivery Service and Store categories as independent variables. This study uses quantitative research by taking data directly from Tokopedia, a total of 160 stores with 80 data from official stores and 80 from non-official stores, and processed using statistical data processing software. This research data were obtained using quantitative methods, with secondary quantitative data from the results of data collection on the first page of the seller/store and the info of the store/merchant/seller Tokopedia based data from 2022. The results of this study are that of the four hypotheses proposed, there are two hypotheses which are stated to have no effect, while the other two hypotheses are stated to have an effect on the dependent variable. The first independent variable has no influence on the dependent variable, so that the H01 hypothesis is partially accepted. The hypothesis that H02 is accepted while Ha2 is rejected is in variable X2 the same as variable X1. Meanwhile, variable X3 has a partial effect on variable Y so that the Ha3 hypothesis is accepted and H03 is rejected. The last hypothesis has been confirmed by Ha4 and H04 is rejected because variable Y is simultaneously influenced by these three factors.